Evaluation of verteporfin pharmakokinetics - redefining the need of photosensitizers in ophthalmology - Ziemssen, Focke; Heimann, Heinrich (Expert opinion on drug metabolism & toxicology, 2012)
Introduction: The benzoporphyrine derivative verteporfin has lost its importance to the treatment of the most frequent neovascular eye diseases. Nevertheless, it is still mandatory to define the remaining applications, role, and potential of verteporfin in ocular photodynamic therapy (PDT), including the dosages of administration, effectiveness, and safety profile. Areas covered: Although verteporfin PDT has forfeited the first-line status and value of treating subfoveal choroidal neovascularization (CNV) due to age-related macular degeneration or pathologic myopia, the treatment remains the standard of care for choroidal haemangioma and polypoidal choroidal vasculopathy. PDT is effective in less pigmented choroidal melanoma as well as in retinal vascular proliferations and retinal angioma. Verteporfin was granted the orphan drug designation for the treatment of chronic or recurrent central serous chorioretinopathy (CSC). Expert opinion: Evidence-based data regarding optimized parameters (low fluence, reduced dose, fractionated irradiation) adapted to the treated diseases (target structure, dosimetry, blood supply) are scarce. Prospective and large clinical trials are missing, although the scientific community agrees on the fact that the standard treatment protocol does not necessarily provide the optimal efficacy to the specific disease or individual patient. Within the reviewed indications, the adverse effect profile is favorable compared with other therapies.